2003
DOI: 10.1085/jgp.200308941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MyBP-C Binding to Actin on Contractility in Heart Muscle

Abstract: In contrast to skeletal muscle isoforms of myosin binding protein C (MyBP-C), the cardiac isoform has 11 rather than 10 fibronectin or Ig modules (modules are identified as C0 to C10, NH2 to COOH terminus), 3 phosphorylation sites between modules C1 and C2, and 28 additional amino acids rich in proline in C5. Phosphorylation between C1 and C2 increases maximum Ca-activated force (Fmax), alters thick filament structure, and increases the probability of myosin heads on the thick filament binding to actin on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
119
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 45 publications
(87 reference statements)
11
119
3
Order By: Relevance
“…The cMyBP-C domains primarily involved in binding actin appear to be the C1 and M-domains (9,15,16,20), although there is evidence that C0 may be important (10,14). Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46).…”
Section: Discussionmentioning
confidence: 99%
“…The cMyBP-C domains primarily involved in binding actin appear to be the C1 and M-domains (9,15,16,20), although there is evidence that C0 may be important (10,14). Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, cMyBP-C AllPϩ was equally effective as endogenous cMyBP-C in maintaining overall myofilament organization and cardiac function. In the absence of cMyBP-C phosphorylation, the C1-C2 domain of cMyBP-C is bound to myosin in the S2 region (21,22), but when phosphorylated, it releases its interaction with myosin, binding to actin (23). Therefore, cMyBP-C probably helps regulate force generation by modulating thick-thin filament interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical evidence implicating an interaction between skeletal myosin-binding protein C and actin thin filaments was reported 30 years ago by Moos et al (12), a finding supported by more recent studies that have narrowed the interactions with actin to the N-terminal regulatory domains of MyBP-C (13,14). Based on X-ray diffraction data from intact skeletal muscle, it has been proposed that the N terminus of MyBP-C interacts with actin (15,16).…”
mentioning
confidence: 83%